Manual del curso dosimetría en radioterapia. Atlas - Gómez, Aristóbulo L.; González, Rubén; Lindenboim, Diana; Mugliaroli, Hugo A.; Ortigueira, Clemente; Papadópulos, Celso C.; Placer, Alejandro E. (Comisión Nacional de Energía Atómica; Argentina, 1973)
Fil: Gómez, Aristóbulo L. Comisión Nacional de Energía Atómica; Argentina